Physical Intelligence: Harness your body's untapped intelligence to achieve more, stress less and live more happily - Claire Dale (Simon & Schuster, 2019)
Do you wish you could be more focused and productive? Would you like to ensure your most confident performance when the stakes are high and your stress levels are even higher? The way your body reacts in any given situation determines your ability to think clearly and your capacity for managing your emotions. When you understand the way your body reacts and how to manage it, your physical intelligence, you can handle that stressful family situation, the make-or-break meeting and the important business presentation. Claire Dale and Patricia Peyton have spent the past thirty years helping business people achieve outstanding success and a deeper sense of fulfilment by applying techniques used by top performers in sport and the arts. This practical guide contains the effective techniques you need to develop your strength, flexibility, resilience and endurance, leaving you feeling confident and fully equipped to deal with whatever comes your way. Each step-by-step strategy can be easily integrated into a busy day and is combined with useful tips and inspiring stories of people who have turned their lives around through physical intelligence.